Comprehensive transcriptome analysis provides molecular insights into the heterosis-associated drought tolerance and reveals ZmbHLH137 that promotes drought tolerance in maize seedlings - Liru Cao; Dongling Zhang; Abbas Muhammad Fahim; Huafeng Liu; Zhe Zhang; Desheng Hu; Feiyu Ye; Chenchen Ma; Salah Fatouh Abou-Elwaf; Nora M. Al Aboud; Yinghui Song; Shulei Guo; et al. (Frontiers in Plant Science)
Drought, a primary environmental factor, imposes significant constraints on maize’s developmental processes and productivity. Heterosis breeding is one of the most important breeding strategies for reducing drought-induced yield losses. The genetic mechanisms of heterosis for drought tolerance in maize remain unclear to date. This study aims to analyze the expression profiles and potential heterosis-related genes of the ZhengDan618 hybrid (F1) and its parents, Zheng8713 (parental parent) and ZhengC126 (maternal parent), with extreme differences in drought tolerance under well-irrigated (WI) and drought-stressed (DS) conditions by RNA-sequencing. F1 plants exhibited the strongest antioxidant enzyme activity and drought tolerance, followed by the parental parent. Transcriptome analysis revealed 1,259 unique differentially expressed genes (DEGs) in the F1 hybrid after drought stress induction, mainly involved in the “Glutathione metabolism” and “Flavonoid biosynthesis” pathways. There were fewer DEGs between the F1 and the parental parent, with the drought tolerance phenotype mostly attributed to the contribution of the drought-tolerant parent Zheng87. The weighted gene co-expression network analysis combined with non-additive gene mining identified 13 non-additive drought stress-associated genes, among them bHLH137 expression exhibited up-regulated expression in response to drought stress. Under drought stress, ZmbHLH137-overexpressing maize plants revealed the lowest H2O2 and MDA content, followed by the B104 WT plants, whereas the zmbhlh137 knockout mutants exhibited the highest H2O2 and MDA content. Moreover, ZmbHLH137-overexpressing maize plants exhibited the higher glutathione peroxidase, catalase, peroxidase, and superoxide dismutase activities, whereas the zmbhlh137 knockout mutants exhibited the lower oxidase activity. These results indicate that ZmbHLH137 positively regulates drought tolerance in maize at the seedling stage by regulating antioxidant enzyme activity. These findings provide novel insights into heterosis regulation in maize seedlings. The identified genes are important genetic resources and may aid strategies for improving drought tolerance in maize.